Navigating High-risk Neonatal Intensive Care Unit (NICU) Care: Insights from the Newborn Behavioral Observation (NBO) - Brambilla, Maria Maddalena; Petrolini, Chiara; Beretta, Virginia; Scarpa, Elena; Moretti, Sabrina; Palanza, Paola; Perrone, Serafina (Current Pediatric Reviews, 2025)
The birth of a baby is a significant milestone for both parents, marking a major life transition into parenthood. In high-risk situations, such as preterm delivery, this event disrupts functional adaptation and greatly impacts parents' ability to recognize and effectively respond to their newborn's physiological and developmental needs. Positive interactions and sensitive responses to an infant's needs enable parents to foster development, supporting regulatory processes and establishing healthy social interaction patterns. The Newborn Behavioral Observation (NBO) Early Intervention is a prevention-focused follow-up program initiated shortly after birth during a developmental window when the infant's brain is highly receptive to environmental influences, maximizing its impact on infant development. Recent applications of the NBO intervention in at-risk contexts have shown promising effects on both infant development and the parent-infant relationship. This educational mini-review aims to summarize the main findings and future prospects of using the NBO to support the transition to parenthood from birth through the first months of life, particularly in high-risk environments such as intensive care units.
Keywords: Preterm birth